Liposome Entrapment of Bacteriophages Improves Wound Healing in a Diabetic Mouse MRSA Infection - Chhibber, Sanjay; Kaur, Jasjeet; Kaur, Sandeep (Frontiers in Microbiology, 2018)
Diabetic populations are more prone to developing wound infections which results in poor and delayed wound healing. Infection with drug resistant organisms further worsen the situation, driving searches for alternative treatment approaches such as phage therapy. Major drawback of phage therapy, however, is low phage persistence in situ, suggesting further refinement of the approach. In the present work we address this issue by employing liposomes as delivery vehicles. A liposome entrapped phage cocktail was evaluated for its ability to resolve a S.aureus-induced diabetic excission wound infection. Two characterized S. aureus specific lytic phages, MR-5 and MR-10 alone, in combination (cocktail), or entrapped in liposomes (versus as free phages) were assesed for their therapeutic efficacy in resolving diabetic wound infection. Mice treated with free phage cocktail showed significant reduction in wound bioburden, greater wound contraction and faster tissue healing than with free monophage therapy. However, to further enhance the availability of viable phages the encapsulation of phage cocktail in the liposomes was done. Results of in vitro stability studies and in vivo phage titer determination, suggests that liposomal entrapment of phage cocktail can lead to better phage persistence at the wound site. A 2 log increase in phage titre, however, was observed at the wound site with liposome entrapped as compared to the free phage cocktail, and this was associaed with increased rates of infection resolution and wound healing. Entrapment of phage cocktails within liposomes thus could represent an attractive approach for treatment of bacterial infections, not responding to antibiotis as increased phage persistence in vitro and in vivo at the wound site was observed.